18F-Fluorodeoxyglucose-Positron Emission Tomography and Pathologic Tumor Size in Early-Stage Invasive Cervical Cancer. Issue 8 (1st November 2009) - Showalter, Timothy N.; Miller, Tom R.; Huettner, Phyllis; Rader, Janet; Grigsby, Perry W.
Abstract : Purpose: Cervical cancer tumor size determined by 18 F-fluorodeoxyglucose-positron emission tomography (FDG-PET) thresholding of the maximum standardized uptake value (SUVMax ) has been correlated with the determined tumor size by computed tomography and magnetic resonance imaging. The purpose of this study was to evaluate the relationship between preoperative FDG-PET tumor size and pathologic tumor diameter in patients with early-stage cervical cancer who were undergoing radical hysterectomy. Patients and Methods: Forty patients with early-stage cervical cancer underwent pretreatment FDG-PET/computed tomography before radical hysterectomy and lymph node dissection. Primary tumor diameter was defined on FDG-PET as the largest diameter of the 3-dimensional volumetric isocontour of the 40% threshold of the SUVMax . The FDG-PET measurements were compared with the tumor diameter and the histological diameter of the pathologic specimen using regression analysis, paired t test, and unpaired t test. Results: The FDG-PET tumor diameter measurements were correlated to the pathologic tumor diameter in the surgical specimen with a coefficient of determination ( R 2 ) of 0.951 and a correlation coefficient of 0.757 ( P < 0.0001). Conclusion: There is a high level of correlation in the FDG-PET and the pathologic tumor measurements in the early-stage cervical cancer.